2020
DOI: 10.1186/s40792-020-0770-y
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium septicum-infected Stanford type A acute aortic dissection: a case report

Abstract: Background: Thoracic aortitis caused by Clostridium septicum is a rare infection with a strong association with malignancy and high mortality rate when left untreated. We report a case of surgical treatment for Stanford type A acute aortic dissection in a patient with C. septicum sepsis and thoracic aortitis. Case presentation: A 63-year-old hypertensive man with rheumatoid arthritis presented with general malaise and diagnosed with C. septicum-infected aortitis with sepsis. On the 5th day of hospitalization, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Our literature search in August 2021 revealed a total of 72 cases of C. septicum –associated aortitis. 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 Thus, the case we have presented is case number 73. Demographically, we found a predisposition for male sex (66.2%), older age (median, 76 years; interquartile range, 67-82 years), gastrointestinal malignancies (52.1%), and diabetes (22.5%).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Our literature search in August 2021 revealed a total of 72 cases of C. septicum –associated aortitis. 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 Thus, the case we have presented is case number 73. Demographically, we found a predisposition for male sex (66.2%), older age (median, 76 years; interquartile range, 67-82 years), gastrointestinal malignancies (52.1%), and diabetes (22.5%).…”
Section: Discussionmentioning
confidence: 96%
“…Antibiotic treatment as the only conservative approach was administered to 23 patients compared with 39 patients who had undergone OAR, 5 patients who had undergone EVAR, and 5 patients whose further treatment was not specified. 14 , 18 , 20 , 21 , 22 , 23 However, to date, the 6-month mortality was 100% for patients receiving conservative treatment (90-day mortality, 84.2%), in contrast to 43.2% for patients undergoing surgery (90-day mortality, 32.1%). 2 , 13 , 16 , 17 , 19 , 21 Regarding OAR, long-term survival (>1 year) was reached for 25% to 50% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…C. septicum is a major etiological agent of nontraumatic or spontaneous gas gangrene, a fulminant form of myonecrosis, in humans (38). The incidence and epidemiology of C. septicum infection in humans is unknown; however, on the basis of case reports, the bacterium can cause aortitis (53)(54)(55)(56)(57)(58), pneumorachis (59,60), meningitis (61), and hepatic abscess (62). These infections can lead to gas gangrene, and even septicemia, with a mortality rate of up to 79% within 48 hours (34).…”
Section: Discussionmentioning
confidence: 99%
“…Infective aortitis can be caused by a number of different organisms, of which Clostridium septicum is one of the least common, 1 but perhaps one of the most virulent. A review of all reported cases of C. septicum aortitis demonstrated this to be the 73rd reported case 2–7 …”
Section: Figmentioning
confidence: 90%
“…A review of all reported cases of C. septicum aortitis demonstrated this to be the 73rd reported case. [2][3][4][5][6][7] C. septicum is a Gram-positive, spore-forming rod, with a strong predisposition to spread throughout the body both via local and haematogenous distribution. 8 Aortic involvement is associated with colonic carcinoma in up to 56%, 2 as its anaerobic growth is facilitated by the hypoxic, necrotic milieu of the tumour.…”
mentioning
confidence: 99%